Pengaruh Trust dan Performance Appraisal Justice terhadap Employee Commitment yang Dimediasi oleh Job Satisfaction pada Tenaga Kesehatan di Jakarta Barat - Emilisa, Netania; Juandra, Diko; Tanuwijaya, Justine; Puspa, Tiara (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the influence of trust and performance appraisal justice variables on employee commitment which is mediated by job satisfaction among health workers in West Jakarta. The data collection method used in this research was a survey using a questionnaire distributed via a Google form link as a data collection tool, and the sample used was 140 people. Data processing methods include test instruments such as validity and reliability tests using SPSS. The results of this research conclude that the job satisfaction variable is able to mediate the influence of the trust variable and the performance appraisal justice variable on employee commitment among health workers in West Jakarta.